2018
DOI: 10.21037/jovs.2018.03.14
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of acute Type A aortic dissection—the Endo Bentall approach

Abstract: Outcome after classical surgical repair of acute Type A aortic dissection has steadily improved over the years and several modifications in cannulation and perfusion added to this achievement. However, subgroups remain where results of classical surgical repair still have room for improvement, particularly patients with severe preoperative malperfusion as well as elderly patients with a limited physiological reserve. So far, only small case series or case reports have been published on the endovascular treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…In open repair for TAAD, AI can be treated using a valve resuspension technique or complete aortic valve replacement. As suggested previously by Kreibich et al 84 and more recently demonstrated by Gaia et al, 85 an “endo‐Bentall” approach might allow for treatment of AI in the setting of TAAD. The authors describe a transapical approach, in which a TAVR valve is deployed simultaneously with an ascending aortic stent graft, successfully extending the proximal landing zone of the stent graft to the aortic annulus.…”
Section: Discussionmentioning
confidence: 76%
“…In open repair for TAAD, AI can be treated using a valve resuspension technique or complete aortic valve replacement. As suggested previously by Kreibich et al 84 and more recently demonstrated by Gaia et al, 85 an “endo‐Bentall” approach might allow for treatment of AI in the setting of TAAD. The authors describe a transapical approach, in which a TAVR valve is deployed simultaneously with an ascending aortic stent graft, successfully extending the proximal landing zone of the stent graft to the aortic annulus.…”
Section: Discussionmentioning
confidence: 76%
“…ステントグラフトの開発は1960年代に端を発し 18), 19), 20),1990年代以降急速に臨床応用が拡がっている 21), 22)。その低侵襲性ゆえに,全身状態の早期安定化および早期治療を求められる多発外傷におけるBTAIに対してもSGは普及しつつある 4), 5), 6), 7), 8)。OSによるBTAIの救命率が70%程度という過去の報告 23), 24)と比較して,SG群の95%を救命し,生存群の91%でSGを選択したという今回の結果も,BTAIに対するSGの優位性を示すものと言える。近年,内因性の大動脈解離に対し解離入口部が大動脈起始部や上行大動脈,大動脈弓部である場合もSGでの修復が試みられつつあり 25), 26), 27), 28), 29),今後,外傷症例全体に対してもSGの適応は拡大していくことが予想される。しかしながら,本研究ではどのような損傷部位・損傷形態であってもBTAIに対してOS,SG双方を選択しうる状況ではなく,上行大動脈から近位大動脈弓損傷においてはOSを選択せざるを得なかったため治療法の適応によるバイアスが排除できておらず,OS群とSG群の治療成績の差異が損傷形態・損傷部位によるものなのか治療方法によるものなのか判定するためには,今後さらなる症例の集積が必要である。…”
Section: 考  察unclassified
“…In 2014, Rylski et al [11] introduced the concept of endovascular treatment of ascending aortic pathologies with valve-carrying conduits associated with an uncovered portion for free diastolic coronary blood flow [11] . Using an endovascular valve-carrying conduit not only resolves the problem of aortic regurgitation, but also effectively results in sufficient anchorage of the device [12] . Alternatively, Nienaber et al [3] proposed a combined TAVR (transcatheter aortic valve replacement)-TEVAR technology, in an attempt to treat variants of aortic dissection including those with compromised aortic valve function.…”
Section: Technical Aspects Of the Procedure: A Review Of The Literaturementioning
confidence: 99%